Moods, Stressors, and Severity of Marital Conflict: A Daily Diary Study of Low‐Income Families. Issue 3 (13th October 2017) - McCormick, Meghan P.; Hsueh, JoAnn; Merrilees, Christine; Chou, Patricia; Mark Cummings, E.
Abstract : Objective: To examine links between negative moods, stressors, and daily marital conflict, and to test whether participation in a family‐strengthening program moderates those associations. Background: Some family‐strengthening interventions have shown positive effects on low‐income married couples' relationships. Yet little is known about how these programs influence low‐income families' daily functioning. Method: Families randomly assigned to the program participated in 10 weeks of relationship education. Control group families received no services. Thirty months later, participants reported on the severity of marital conflicts over a 15‐day period, as well as their moods and stressors. Results: Dyadic models demonstrated that although moods like anger, anxiety, stress, and sadness were associated with more severe marital disagreements, associations were less strong for wives assigned to the program than to the control group. Although stress related to money was associated with more severe disagreements for husbands, associations were weaker for husbands assigned to the program than for those to the control group. Conclusion: Family‐strengthening interventions may be able to reduce the tendency for negative moods and stressors to manifest in more severe marital conflict. Implications: Programs may benefit from explicitly addressing the moods and stressors that individual husbands and wives report experiencing in their daily lives.